Pemetaan Prevalensi Balita Gizi Buruk di Provinsi Jawa Timur Tahun 2014 dengan Mixed Geographically Weighted Regression (MGWR) - elvira mustikawati putri hermanto (Faculty of Science and Technology, Univ. PGRI Adi Buana Surabaya, 2017)
Based on Indonesia Health Profile data, In 2014 East Java Province is in the first place of malnutrition in Indonesia. Efforts have been made by the provincial government as an effort to improve nutrition by specific interventions (health) and sensitive (non-health) interventions. As an effort to suppress malnutrition case in East Java Province, this research is done to know the factors that influence to percentage of malnourished children under five in each regency / city as well as globally influential factor in East Java Province. The method used is Mixed Geographically Weighted Regression (MGWR). Based on the results of analysis with MGWR, it is known that the variables that affect globally are variables X7 and X10, while the variables that affect locally is variable X1. However, based on model goodness test with R2 criteria, it is known that MGWR model is not better than GWR model. The value of R2of MGWR is 53.60% while R2of GWR is 61.53%.